B-mode ultrasonographic measurement of inferior vena cava diameter among healthy adults in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The inferior vena cava (IVC) is thin-walled compliant vessel that adjust the body volume status by changing its diameter depending on the total body fluid volume. sonographic measurement of IVC diameter has been reported as an alternative, rapid and non-invasive method of volume assessment of body fluids. The aim of this study is to determine the normal IVC diameter among healthy adults in Kano, Nigeria.Materials and Methods:Sonographic measurement of IVC of healthy adults with age ranging between 15 and 65 years was done with the subject in the supine position. The intrahepatic portion of its diameter was measured at about 2 cm proximal to the hepatic veins in a longitudinal plane in both inspiratory and expiratory phases of respiration. Three repeated measurements were done to reduce intra-observer variability in this prospective cross-sectional study.Results:A total of 400 adults comprising 173 (43.3%) males and 227 (56.8%) females were recruited using Fisher's statistical formula for sample size determination. The mean age of the subjects was 32.4 ± standard deviation 10.9 years. The mean inspiratory diameter was 10.1 ± 2.7 mm (ranging from 4.8 mm to 18.8 mm). The overall mean IVC expiratory (IVCexp) diameter in this study was 16.7 ± 2.7 mm (range = 10.9–25.4 mm). The mean IVCexp diameter was slightly higher for males than for females (males: 17.1 ± 2.8 mm; females: 16.3 ± 2.7 mm). This difference was statistically significant (P= 0.0022). There was a gradual decrease in IVC diameter with advancing age.Conclusion:This study was able to generate normal IVC diameter in a sample of Nigerians which may serve as a reference for normal values in Black Africans.